A Review in Managing Cloud computing Security Issues and Future Research - Raad, Wisam (Opción, 2019)
Cloud computing is one of the most creative technical developments in the technology breakthrough era. It facilitates all aspects of life from business to social and family life. The rapidly growth of international businesses and the bomb of technological revolution in terms of adopting smart cities and governments, e-commerce and e-learning and etc., gave cloud computing a momentum because to can overcome the barriers of knowledge storage and transform in huge quantity. This made cloud computing topic one of the hot- test in the literature. However, the popularity of cloud computing is not im- mune of risks, especially in security, which leaves a negative effect on the use of cloud computing. But also there is no way to avoid using cloud computing because it is the key driver for smoothening knowledge sharing and storage. Thus, academics and information technology developers are struggling hard to find solution for cloud security issues. In this paper, overview bout cloud computing issues will be discussed and commendations that need to be taken by future research to address those issues will be raised.